The artistry of therapy and Zen practice. (2nd July 2016) - Webb, Julie
ABSTRACT: At a time when to become a therapist we may be required to measure our empathy against some sort of growth chart, we may also be witnessing the emergence of a radical battle against such systemizing of subtle and natural human capacities. This discussion will offer a description of the process of becoming and the actualizing tendency, as trust and faith in the subtle and natural opening of the true dharma eye . Zen writings often engage with the challenge of our ability to notice what is right before our eyes and perhaps as therapists our task is to be open, receptive and awake to the intimacy of phenomena in order that we may aid a person, who for whatever reason, may have their eyes closed. Openness and receptivity may help nurture a creative feedback loop that is inherent in human relating but often unacknowledged explicitly in therapy, and everyday living. This explicit acknowledgement may also correspond with notions of non-conscious affect and affective resonance .